Rapid assessment of surface-water flood-management options in urban catchments. Issue 3 (16th March 2018) - Webber, J. L.; Gibson, M. J.; Chen, A. S.; Savic, D.; Fu, G.; Butler, D.
Abstract: Surface-water flooding in urban areas has become a pressing issue due to changing precipitation patterns, expanding urban areas and ageing drainage infrastructure. Selection of flood-management options for widespread implementation using quantitative performance measures is both technically and computationally demanding, which limits the evidence available for decision support. This study presents a new framework for surface-water flood-intervention assessment at high resolution. The framework improves computational efficiency through utilisation of accessible data, simplified representations of interventions and a resource efficient cellular automata flood model. The advantages of this framework are demonstrated through an example case study where the performance of 12 high-level intervention strategies has been evaluated. Results from the case study demonstrate that the framework is able to provide quantitative performance values for a range of interventions. The speed of analysis supports the application of the framework as a decision-making tool for urban water planning.